AYAT-AYAT TAMTSÃL AL-QUR`AN (ANALISIS STILISTIKA) - Bustami, Hafni (Institut Agama Islam Negeri Imam Bonjol Padang, 2013)
The Quran is the highest miracle (mu`jizat) of Prophet Muhammad (Peace be upon Him). Its strength lies in two aspects; content and linguistic. The God and the Prophet have encouraged the Moslem to comprehend similitude verses of the Quran (tamtsÃ®l) since it provides countless benefits. It is found through this research that the style of similitude verses (sharÃ®h, mursal and kÃ¢minah) were written in 168 verses. Based on the language style, tamtsÃ®l is classified into sharÃ®h, mursal dan kÃ¢minah.Â Meanwhile, the benefits of the similitude verses for mankind are: targhÃ®b, tarhÃ®b, tahzÃ®r, mauâizhah and iâtibÃ¢r.